Exploring Women’s Relationships: An analysis of Malaysian Women’s Lifestyle Magazines - Hashim, Intan Hashimah Mohd; Endut, Noraida; Azmawati, Azman Azwan (Universiti Sains Malaysia, 2016)
This study presented content analysis of two women’s lifestyle magazines for the period of January until June 2016. Combining media studies and relationship research, this paper examined cover pages and cover stories of two highly popular and widely circulated women’s lifestyle magazines in Malaysia; Nona and Wanita. Preliminary analysis indicated women who appeared in the cover page and cover story of the two magazines were attractive, successful and that they held prominent positions within society. They included businesswomen, actresses and politicians/activists. Women’s relationships, as portrayed in these magazines, comprised of children, husbands and family and this is consistent with their private roles as mothers, wives, sisters and daughters. From the analysis, women in the cover pages of these two magazines continued to be presented in traditional and patriarchal gender roles including being nurturant and submissive with an emphasis on their sexuality. This is in spite of them holding non-traditional roles as providers and representing success stories of women in public domain. The analysis provided supports that gender roles and cultural expectations continue to influence people’s social experiences. In addition, these gender roles cultural expectations also shape and at the same time enhanced by the representations in the media.